A Novel Porous Carrier Found in Nature for Nanocomposite Materials Preparation: A Case Study of Artemia Egg Shell-Supported TiO2 for Formaldehyde Removal. (13th August 2015) - Wang, Sufeng; Lv, Fengjing; Jiao, Tifeng; Ao, Jingfen; Zhang, Xiaochun; Jin, Fengdan
Abstract : Artemia egg shells have an asymptotic sized pore structure (pore diameter: 500 nm–2500 nm), which could be used as a porous carrier for the preparation of nanocomposite materials. The objective of the present study was to prepare shell-supported TiO2 using a naturally porous carrier, Artemia egg shell, and to exhibit a case study of shell-supported TiO2 for formaldehyde removal. Characterization of shell-TiO2 using SEM-EDS, TEM, and XRD proved that Artemia shell with asymptotic reduction pores (pore diameter: 500 nm–2500 nm) can be used as the carrier for nanocomposite materials. Artemia egg shell-supported TiO2 in polycrystalline-like nanostructures can be used for the high efficiency removal (adsorption and degradation) of formaldehyde under visible light. Our results suggest that iron, one of the shell's components, should broaden the absorption of visible light and enhance the photocatalytic efficiency of nanotitanium dioxide under visible light. Due to their interesting absorption and formaldehyde removal qualities, Artemia egg shell, as a novel naturally porous carrier for nanocomposite materials preparation, especially in the preparation of nanocatalysts, is worthy of further study.